Systematics and evolution of Escovopsis and hypocrealean relatives associated with attine ant colonies - Montoya, Quimi Vidaurre [UNESP] (2020)
Escovopsis is a group of fungi that inhabit the colonies of fungus-growing ants. The study of this fungal genus has been based on several assumptions that became dogmas. For instance, i) many fungi associated with attines were treated as Escovopsis, without taxonomic support, ii) the genus was considered a specialized mycoparasite of the attines’ mutualistic fungi, and iii) it was thought that the genus coevolved with attines based on the assumption of its parasitic lifestyle. However, for many years the Escovopsis taxonomy, its relationship with the ants and its phylogeographic distribution were almost an empty space for the scientific community. In addition, the origin of the genus was never addressed. Therefore, the main objective of this study was to build the systematics of the Escovopsis and shed light on its origin, evolution, diversification, and phylogeographic distribution. Three manuscripts are the result of this study and are presented here as chapters. The first manuscript presents the description of two new Escovopsis species (published in MycoKeys). The second manuscript brings the reassessment of the Escovopsis taxonomy, provides a suitable taxonomic and phylogenetic framework for the systematics of the genus, and describes two new Hypocreaceae genera (submitted to IMA Fungus). The third manuscript shows the origin, evolution, phylogeographic distribution and the trait adaptations experienced by Escovopsis since its entry in fungus-growing ant colonies. This study fills an important gap in the taxonomy, systematics, and evolution of Escovopsis and related genera which certainly will help researchers to better understand the evolution of the attines’ system.